Filipino working adolescents' conception of work - Yabut, Homer J.; Amarmani, Rajiv; Mendoza, Roberto; Lee, Chester Howard; Valencia, Marshall N. (Quezon City Psychological Association of the Philippines.)
"The present study seeks to determine these adolescents' conceptions of the meanings of, reasons for, and contributions to their work. Findings across rural and urban groups show that Filipino working adolescents give meaning to work as sustenance. They work because of financial difficulty. One positive benefit of work is being able to support one's family, while the negative contributions of work include compromised studies, compromised self-fulfillment, and compromised health. Rural adolescents approach work as a means to maintaining their survival and lifestyles, whereas urban adolescents approach work as a means to growth."
Keywords: Filipino working adolescents; Conceptions of work; Focus group Discussion; Positive youth development